Circular polarizer
The circular polarizing plate, with its optimized layer structure, addresses the issue of reflected light and color changes in vehicle displays, enhancing safety and light resistance for on-vehicle applications.
Patent Information
- Application Number
- JP2023182920
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2039-12-11
AI Technical Summary
Image display devices equipped with circular polarizers, used in vehicles, face issues with reflected light from the display being reflected by the windshield, leading to potential safety hazards due to significant color changes and light reflection when viewed from different angles.
A circular polarizing plate is designed with a specific layer structure, comprising a first optically anisotropic layer, a polarizer, and a second optically anisotropic layer, optimized to reduce reflected light and color changes when display light is reflected by the windshield, while maintaining excellent light resistance.
The circular polarizing plate effectively reduces reflected light and color changes when viewed from different angles, enhancing driving safety and maintaining excellent light resistance, making it suitable for on-vehicle display applications.
Smart Images

Figure 0007664992000009 
Figure 0007664992000010 
Figure 0007664992000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a circular polarizing plate, and further to an organic electroluminescence (hereinafter also referred to as organic EL) display device equipped with a circular polarizing plate. [Background technology]
[0002] In recent years, image display devices, such as organic electroluminescence (EL) display devices, have rapidly become widespread. In general, an organic EL display device is equipped with a circular polarizing plate having a polarizer and a λ / 4 plate in this order from the viewing side. Patent Document 1 proposes a λ / 4 plate formed from a composition containing a liquid crystal compound. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-187717 A Summary of the Invention [Problem to be solved by the invention]
[0004] Image display devices equipped with circular polarizing plates are sometimes used as in-vehicle displays. When such displays are turned on inside a vehicle at night, the light from the display may be reflected by the windshield, and the color of the reflected light may change significantly depending on the viewing angle, which may impair driving safety.
[0005] The present invention aims to provide a circular polarizing plate suitable for in-vehicle displays, which reduces reflected light when display light is reflected on the windshield inside the vehicle, reduces color change in the reflected light, and has excellent light resistance. [Means for solving the problem]
[0006] The present invention provides the following circular polarizing plate and organic electroluminescent display device. [1] A circularly polarizing plate having, from a viewing side, a first optically anisotropic layer, a polarizer, and a second optically anisotropic layer in this order, The first optically anisotropic layer is represented by the following formulas (I), (II) and (III): Re(450) / Re(550)≦1.00 (I) 1.00≦Re(650) / Re(550) (II) 90nm≦Re(550)≦180nm (III) [wherein Re(450) represents an in-plane retardation value of the optically anisotropic layer at a wavelength of 450 nm; Re(550) represents the in-plane retardation value of the optically anisotropic layer at a wavelength of 550 nm; Re(650) represents the in-plane retardation value of the optically anisotropic layer at a wavelength of 650 nm. The optical property is represented by A circularly polarizing plate, wherein the first optically anisotropic layer and the second optically anisotropic layer are layers containing a polymer formed by polymerizing a polymerizable liquid crystal compound in an aligned state. [2] The circularly polarizing plate according to [1], wherein the second optically anisotropic layer has the optical property represented by formula (III). [3] The circularly polarizing plate according to [1] or [2], wherein the second optically anisotropic layer further has the formula (I) and the formula (II). [4] The following formula (IV): 200nm≦Re(550)≦320nm (IV) The circularly polarizing plate according to any one of [1] to [3], further comprising a third optically anisotropic layer having optical properties represented by the formula: [wherein Re(550) represents an in-plane retardation value of the optically anisotropic layer at a wavelength of 550 nm]. [5] The circularly polarizing plate according to any one of [1] to [4], wherein the angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer is 90°±10°. [6] The circularly polarizing plate according to any one of [1] to [5], wherein the polarizer is a polarizer in which a dichroic dye is adsorbed and aligned on a uniaxially stretched polyvinyl alcohol-based resin film. [7] The circularly polarizing plate according to any one of [1] to [5], wherein the polarizer is a polarizer in which a dichroic dye is oriented in a cured film formed by polymerizing a polymerizable liquid crystal compound. [8] An organic electroluminescence display device comprising the circular polarizing plate according to any one of [1] to [7]. [9] An in-vehicle display comprising the organic electroluminescence display device according to [8]. Effect of the Invention
[0007] According to the present invention, it is possible to provide a circular polarizing plate suitable for in-vehicle displays, which reduces the reflected light when the in-vehicle display light is reflected on the windshield, reduces the color change of the reflected light, and has excellent light resistance. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a schematic cross-sectional view showing a layer structure of a circular polarizing plate. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a layer structure of a circular polarizing plate. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing a layer structure of a circular polarizing plate. [Figure 4] FIG. 2 is a schematic cross-sectional view showing a layer structure of a circular polarizing plate. [Diagram 5] FIG. 2 is a schematic cross-sectional view showing a layer structure of a circular polarizing plate. [Figure 6] 1 is a schematic cross-sectional view illustrating an example of a method for producing a circularly polarizing plate. [Figure 7] FIG. 1 is a schematic cross-sectional view illustrating an example of a layer structure of an organic EL display device. [Figure 8] FIG. 1 is a schematic diagram showing a method for evaluating reflected light of a display. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiment. In all of the drawings, the scale of each component is appropriately adjusted to make it easier to understand, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component.
[0010] <Circular polarizing plate> The circularly polarizing plate of the present invention has a first optically anisotropic layer, a polarizer, and a second optically anisotropic layer in this order. The first optically anisotropic layer, the second optically anisotropic layer, and the polarizer can be laminated, for example, via an adhesive layer described later.
[0011] An example of the layer structure of the circular polarizer of the present invention will be described below with reference to Fig. 1. The circular polarizer 100 shown in Fig. 1 has a layer structure in which a first optically anisotropic layer 11, a polarizer 10, and a second optically anisotropic layer 12 are laminated in this order from the viewing side. The viewing side refers to the side of the circular polarizer 100 opposite to the image display element side when the circular polarizer 100 is applied to an image display device.
[0012] Circularly polarizing plate 100 may have layers other than the layers shown in Fig. 1. Examples of layers that circularly polarizing plate 100 may further have include a front plate, a protective film, a light-shielding pattern, and an adhesive layer.
[0013] The shape of the main surface of the circular polarizing plate 100 may be substantially rectangular. The main surface means the surface having the widest area corresponding to the display surface. Being substantially rectangular means that at least one of the four corners (corners) may be cut or rounded to form an obtuse angle, a part of an end face perpendicular to the main surface may have a recessed part (notch) recessed in the in-plane direction, or a part of the main surface may have a hole cut out in the shape of a circle, an ellipse, a polygon, or a combination thereof.
[0014] There is no particular limitation on the size of the circular polarizing plate 100. When the circular polarizing plate 100 is substantially rectangular, the length of the long side is preferably 6 cm or more and 35 cm or less, more preferably 10 cm or more and 30 cm or less, and the length of the short side is preferably 5 cm or more and 30 cm or less, more preferably 6 cm or more and 25 cm or less.
[0015] (Optical anisotropic layer) The first optically anisotropic layer 11 is disposed on the viewing side of the second optically anisotropic layer 12 in the circular polarizing plate 100. The first optically anisotropic layer 11 has optical properties represented by the formulas (I), (II) and (III). Re(450) / Re(550)≦1.00 (I) 1.00≦Re(650) / Re(550) (II) 90nm≦Re(550)≦180nm (III) [wherein Re(450) represents an in-plane retardation value of the optically anisotropic layer at a wavelength of 450 nm; Re(550) represents the in-plane retardation value of the optically anisotropic layer at a wavelength of 550 nm; Re(650) represents the in-plane retardation value of the optically anisotropic layer at a wavelength of 650 nm. The in-plane retardation value is defined by the following formula. Re(λ)=(nx(λ)-ny(λ))×d (wherein Re(λ) represents an in-plane retardation value at a wavelength of λ nm of the optically anisotropic layer, d represents a thickness of the optically anisotropic layer, nx represents a principal refractive index at a wavelength of λ nm in a direction parallel to the plane of the optically anisotropic layer in the index ellipsoid formed by the optically anisotropic layer, and ny represents a refractive index at a wavelength of λ nm in a direction parallel to the plane of the optically anisotropic layer and perpendicular to the direction of nx in the index ellipsoid formed by the optically anisotropic layer.)
[0016] The first optically anisotropic layer 11 can have reverse wavelength dispersion by having the optical properties represented by formulas (I) and (II). The first optically anisotropic layer 11 preferably has the optical properties represented by formula (I-1), and more preferably has the optical properties represented by formula (I-2). Re(450) / Re(550)≦0.93 (I-1) 0.81≦Re(450) / Re(550) (I-2)
[0017] The first optically anisotropic layer 11 preferably has optical properties represented by formula (II-1), and more preferably has optical properties represented by formula (II-2). 1.00 <Re(650) / Re(550) (II-1) Re(650) / Re(550)≦1.10 (II-2)
[0018] The first optically anisotropic layer 11 preferably has optical properties represented by formula (III-1), and more preferably has optical properties represented by formula (III-2). 100nm≦Re(550)≦160nm (III-1) 110nm≦Re(550)≦150nm (III-2) When the first optically anisotropic layer 11 has the above optical properties, color change or coloring tends to be small when the display device is viewed obliquely.
[0019] The second optically anisotropic layer 12 can have optical properties represented by formula (III). The second optically anisotropic layer 12 preferably has optical properties represented by formula (III-1), and more preferably has optical properties represented by formula (III-2). The second optically anisotropic layer 12 can have reverse wavelength dispersion by further having the optical properties represented by formula (I) and formula (II). The second optically anisotropic layer 12 preferably has the optical properties represented by formula (I-1), more preferably has the optical properties represented by formula (I-2). The second optically anisotropic layer 12 preferably has the optical properties represented by formula (II-1), more preferably has the optical properties represented by formula (II-2). When the second optically anisotropic layer 12 has the above optical properties, color change or coloring tends to be small when the display device is viewed obliquely.
[0020] The circular polarizer has the formula (IV): 200nm≦Re(550)≦320nm (IV) In the formula, Re(550) represents the in-plane retardation value of the optically anisotropic layer at a wavelength of 550 nm.
[0021] The third optically anisotropic layer is preferably an optically anisotropic layer having optical properties represented by formula (IV-1), and more preferably an optically anisotropic layer having optical properties represented by formula (IV-2). 250nm≦Re(550)≦300nm (IV-1) 265nm≦Re(550)≦285nm (IV-2)
[0022] The third optically anisotropic layer is represented by formula (V): nx≒ny <nz (V) The optical properties represented by the formula (1) can be expressed as follows: nx represents the principal refractive index in a direction parallel to the plane of the optically anisotropic layer in the refractive index ellipsoid formed by the optically anisotropic layer. ny represents the refractive index in a direction parallel to the plane of the optically anisotropic layer and perpendicular to the direction of nx in the refractive index ellipsoid formed by the optically anisotropic layer. nz represents the refractive index in a direction perpendicular to the plane of the optically anisotropic layer in the refractive index ellipsoid formed by the optically anisotropic layer.
[0023] When the circular polarizer 100 has a third optically anisotropic layer, the third optically anisotropic layer can be located between the polarizer 10 and the second optically anisotropic layer 12, or on the side of the second optically anisotropic layer 12 opposite the polarizer 10 side.
[0024] The first optically anisotropic layer 11, the second optically anisotropic layer 12 and the third optically anisotropic layer may each include an alignment film which will be described later.
[0025] The first optically anisotropic layer 11 is preferably a retardation layer having reverse wavelength dispersion and imparting a retardation of λ / 4. The second optical anisotropic layer 12 can be a retardation layer such as a layer that provides a retardation of, for example, λ / 4 (positive A layer), a layer that provides a retardation of λ / 2, and a positive C layer. The second optical anisotropic layer 12 is preferably a layer that provides a retardation of λ / 4, more preferably a retardation layer that has reverse wavelength dispersion and provides a retardation of λ / 4. The third optical anisotropic layer can be a retardation layer such as a layer that provides a retardation of λ / 2 and a positive C layer. The third optical anisotropic layer is preferably a layer that provides a retardation of λ / 2.
[0026] The layer that provides a retardation of λ / 4 means a layer in which the in-plane retardation value at a wavelength of 550 nm is preferably 90 nm or more and 180 nm or less, more preferably 100 nm or more and 160 nm or less, and even more preferably the in-plane retardation value is 110 nm or more and 150 nm or less. The layer that provides a retardation of λ / 2 means a layer in which the in-plane retardation value at a wavelength of 550 nm is preferably 200 nm or more and 320 nm or less, more preferably the in-plane retardation value is 250 nm or more and 300 nm or less, and even more preferably the in-plane retardation value is 265 nm or more and 285 nm or less. The positive C layer can be a layer that exhibits a refractive index relationship of nx≒ny < nz. The retardation value in the thickness direction of the positive C layer can be -150 nm or more and -30 nm or less, and can be -120 nm or more and -50 nm or less at a wavelength of 550 nm.
[0027] Note that the retardation value in the thickness direction is defined by the following formula. Rth(λ)=[{nx(λ)+ny(λ)} / 2 - nz(λ)]×d [In the formula, Rth(λ) represents a retardation value in the thickness direction of the optically anisotropic layer at a wavelength of λ nm, d represents the thickness of the optically anisotropic layer, nx(λ) represents the principal refractive index at a wavelength of λ nm in a direction parallel to the plane of the optically anisotropic layer in the refractive index ellipsoid formed by the optically anisotropic layer, ny(λ) represents the refractive index at a wavelength of λ nm in a direction parallel to the plane of the optically anisotropic layer and perpendicular to the direction of nx(λ), and nz(λ) represents the refractive index at a wavelength of λ nm in a direction perpendicular to the film plane in the refractive index ellipsoid formed by the optically anisotropic layer.]
[0028] From the viewpoint of functioning as a circular polarizing plate, the slow axes of the first optically anisotropic layer 11 and the second optically anisotropic layer 12 may form an angle of, for example, 45°±10° with the absorption axis of the polarizer 10, preferably 45°±5°, and more preferably 45°±2°.
[0029] From the viewpoint of suppressing curling, the angle between the slow axis of the first optically anisotropic layer 11 and the slow axis of the second optically anisotropic layer 12 is preferably 90°±15°, more preferably 90°±10°, even more preferably 90°±5°, and particularly preferably 90°.
[0030] When the second optically anisotropic layer 12 has the optical properties represented by formula (III), preferably, the angle between the slow axis of the second optically anisotropic layer 12 and the absorption axis of the polarizer 10 is 45°, and the angle between the slow axis of the first optically anisotropic layer 11 and the slow axis of the second optically anisotropic layer 12 is 90°.
[0031] The first optically anisotropic layer 11 and the second optically anisotropic layer 12 are layers containing a polymer formed by polymerizing a polymerizable liquid crystal compound in an aligned state (hereinafter, also referred to as a cured layer). When the circularly polarizing plate includes a third optically anisotropic layer, the third optically anisotropic layer may be a cured layer. The cured layer is formed, for example, on an alignment film provided on a substrate. The substrate may be a substrate having a function of supporting the alignment film and formed in a long length. This substrate functions as a releasable support and can support the cured layer for transfer. Furthermore, it is preferable that the surface of the substrate has an adhesive strength sufficient to enable peeling. Examples of the substrate include resin films exemplified as materials for the protective film described later. The substrate and the alignment film may be included in a circularly polarizing plate. The alignment film may be removed together with the substrate when the substrate is removed. When the first optically anisotropic layer 11 includes a cured material layer and satisfies the above formulas (I), (II) and (III), it becomes possible to reduce the reflected light when the in-car display light is reflected by the windshield and to reduce the color change of the reflected light, and the light resistance of the circular polarizing plate tends to be improved.
[0032] The thickness of the substrate is not particularly limited, but may be, for example, in the range of 20 μm to 200 μm. When the thickness of the substrate is 20 μm or more, strength tends to be easily imparted. On the other hand, when the thickness is 200 μm or less, when the substrate is cut into a sheet of substrate, an increase in processing waste and wear of the cutting blade tend to be easily suppressed.
[0033] The substrate may be subjected to various anti-blocking treatments. Examples of the anti-blocking treatment include an easy-adhesion treatment, a treatment for kneading a filler or the like, and an embossing (knurling) treatment. By subjecting the substrate to such an anti-blocking treatment, it is possible to effectively prevent the substrates from sticking to each other when the substrates are wound up, that is, so-called blocking, and it is possible to produce an optical film with high productivity.
[0034] The cured layer is formed on the substrate via the alignment film, that is, the substrate and the alignment film are laminated in this order, and the layer of the cured polymerizable liquid crystal compound is laminated on the alignment film.
[0035] The alignment film is not limited to a vertical alignment film, and may be an alignment film that aligns the molecular axis of the polymerizable liquid crystal compound horizontally, or may be an alignment film that aligns the molecular axis of the polymerizable liquid crystal compound at an angle. The alignment film is preferably one that has solvent resistance that does not dissolve the composition containing the polymerizable liquid crystal compound described later by coating, etc., and also has heat resistance in the heat treatment for removing the solvent and orienting the polymerizable liquid crystal compound. Examples of the alignment film include an alignment film containing an orienting polymer, a photoalignment film, and a groove alignment film that forms a concave-convex pattern or a plurality of grooves on the surface to achieve alignment. The thickness of the alignment film is usually in the range of 10 nm to 10,000 nm, preferably in the range of 10 nm to 1000 nm, more preferably in the range of 500 nm to 500 nm, and even more preferably in the range of 10 nm to 20 nm.
[0036] The resin used for the alignment film is not particularly limited as long as it is a resin used as a material for known alignment films, and a cured product obtained by curing a conventionally known monofunctional or polyfunctional (meth)acrylate monomer under a polymerization initiator, etc., can be used. Specifically, examples of the (meth)acrylate monomer include 2-ethylhexyl acrylate, cyclohexyl acrylate, diethylene glycol mono 2-ethylhexyl ether acrylate, diethylene glycol monophenyl ether acrylate, tetraethylene glycol monophenyl ether acrylate, trimethylolpropane triacrylate, lauryl acrylate, lauryl methacrylate, isobornyl acrylate, isobornyl methacrylate, 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxypropyl acrylate, benzyl acrylate, tetrahydrofurfuryl methacrylate, 2-hydroxyethyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, methacrylic acid, and urethane acrylate. As the resin, one of these may be used alone, or a mixture of two or more may be used.
[0037] Although the type of polymerizable liquid crystal compound is not particularly limited, it can be classified into rod-shaped type (rod-shaped liquid crystal compound) and discotic type (discotic liquid crystal compound) based on its shape. Furthermore, there are low molecular type and polymer type. Note that polymer generally refers to a polymer having a degree of polymerization of 100 or more (Polymer Physics, Phase Transition Dynamics, Masao Doi, page 2, Iwanami Shoten, 1992). In this embodiment, any polymerizable liquid crystal compound can be used. Furthermore, two or more rod-shaped liquid crystal compounds, two or more discotic liquid crystal compounds, or a mixture of a rod-shaped liquid crystal compound and a discotic liquid crystal compound may be used.
[0038] As the rod-shaped liquid crystal compound, for example, those described in claim 1 of JP-T-11-513019 or those described in paragraphs
[0026] to
[0098] of JP-A-2005-289980 can be preferably used. As the discotic liquid crystal compound, for example, those described in paragraphs
[0020] to
[0067] of JP-A-2007-108732 or those described in paragraphs
[0013] to
[0108] of JP-A-2010-244038 can be preferably used.
[0039] The polymerizable liquid crystal compound has a polymerizable group capable of undergoing a polymerization reaction. As the polymerizable group, for example, a functional group capable of an addition polymerization reaction, such as a polymerizable ethylenically unsaturated group or a ring-polymerizable group, is preferable. More specifically, as the polymerizable group, for example, a (meth)acryloyl group, a vinyl group, a styryl group, an allyl group, etc. can be mentioned. Among them, a (meth)acryloyl group is preferable. Note that the (meth)acryloyl group is a concept that includes both a methacryloyl group and an acryloyl group.
[0040] Two or more kinds of polymerizable liquid crystal compounds may be used in combination, and in this case, at least one of them may have two or more polymerizable groups in the molecule. After the polymerizable liquid crystal compound becomes a polymer, it is no longer necessary to show liquid crystallinity. The polymerizable liquid crystal compounds used to form the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer may be the same polymerizable liquid crystal compound, or may be different polymerizable liquid crystal compounds.
[0041] As described later, the cured product layer can be formed by, for example, applying a composition containing a polymerizable liquid crystal compound (hereinafter, also referred to as a polymerizable liquid crystal composition) onto an alignment film and curing it by irradiating it with active energy rays. The polymerizable liquid crystal composition may contain components other than the above-mentioned polymerizable liquid crystal compound. For example, the polymerizable liquid crystal composition preferably contains a polymerization initiator. The polymerization initiator used is, for example, a thermal polymerization initiator or a photopolymerization initiator, selected according to the type of polymerization reaction. For example, the photopolymerization initiator may be an α-carbonyl compound, an acyloin ether, an α-hydrocarbon-substituted aromatic acyloin compound, a polynuclear quinone compound, or a combination of a triaryl imidazole dimer and a p-aminophenyl ketone. The amount of the polymerization initiator used is preferably 0.01% by mass or more and 20% by mass or less, more preferably 0.5% by mass or more and 5% by mass or less, based on the total solid content in the polymerizable liquid crystal composition.
[0042] In addition, the polymerizable liquid crystal composition may contain a polymerizable monomer from the viewpoint of uniformity of the coating film and strength of the film. The polymerizable monomer may be a radically polymerizable or cationic polymerizable compound. Among them, a polyfunctional radically polymerizable monomer is preferable.
[0043] The polymerizable monomer is preferably one that can be copolymerized with the above-mentioned polymerizable liquid crystal compound. The amount of the polymerizable monomer used is preferably 1% by mass or more and 50% by mass or less, more preferably 2% by mass or more and 30% by mass or less, based on the total mass of the polymerizable liquid crystal compound.
[0044] The polymerizable liquid crystal composition may contain a surfactant from the viewpoint of uniformity of the coating film and strength of the film. Examples of the surfactant include conventionally known compounds. Among them, fluorine-based compounds are particularly preferable.
[0045] The polymerizable liquid crystal composition may contain a solvent, and an organic solvent is preferably used. Examples of the organic solvent include amides (e.g., N,N-dimethylformamide), sulfoxides (e.g., dimethyl sulfoxide), heterocyclic compounds (e.g., pyridine), hydrocarbons (e.g., benzene, hexane), alkyl halides (e.g., chloroform, dichloromethane), esters (e.g., methyl acetate, ethyl acetate, butyl acetate), ketones (e.g., acetone, methyl ethyl ketone), and ethers (e.g., tetrahydrofuran, 1,2-dimethoxyethane). Among these, alkyl halides and ketones are preferred. Two or more organic solvents may be used in combination.
[0046] The polymerizable liquid crystal composition may also contain various alignment agents, such as a vertical alignment promoter such as a polarizer interface side vertical alignment agent and an air interface side vertical alignment agent, and a horizontal alignment promoter such as a polarizer interface side horizontal alignment agent and an air interface side horizontal alignment agent. Furthermore, the polymerizable liquid crystal composition may also contain an adhesion improver, a plasticizer, a polymer, etc., in addition to the above components.
[0047] The active energy rays include ultraviolet rays, visible light, electron beams, and X-rays, and are preferably ultraviolet rays. Examples of the light source of the active energy rays include a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 44 nm, a chemical lamp, a black light lamp, a microwave excited mercury lamp, and a metal halide lamp.
[0048] The UV irradiation intensity is usually 100mW / cm 2 More than 3,000mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating a cationic polymerization initiator or a radical polymerization initiator. The ultraviolet irradiation time is usually 0.1 seconds or more and 10 minutes or less, preferably 0.1 seconds or more and 5 minutes or less, more preferably 0.1 seconds or more and 3 minutes or less, and further preferably 0.1 seconds or more and 1 minute or less.
[0049] The ultraviolet light can be irradiated once or in multiple separate steps. It is preferable to irradiate the ultraviolet light multiple times. When the polymerization rate of the liquid crystal compound is increased, the puncture modulus tends to increase. Although it depends on the polymerization initiator used, the integrated light amount at a wavelength of 365 nm is 700 mJ / cm. 2 More preferably, it is 1,100 mJ / cm or more. 2 More preferably, it is 1,300 mJ / cm or more. 2 It is more preferable that the integrated light amount is 2,000 mJ / cm or more. The integrated light amount is advantageous for increasing the polymerization rate of the polymerizable liquid crystal compound constituting the optically anisotropic layer. The integrated light amount at a wavelength of 365 nm is 2,000 mJ / cm or more. 2 It is preferable to set the dose to 1,800 mJ / cm or less. 2 It is more preferable that the integrated light amount is set to the above range.
[0050] In addition, in order to prevent the alignment of the liquid crystal compound from being disturbed by heat immediately after the ultraviolet irradiation, it is preferable to provide a cooling step after the ultraviolet irradiation. By providing a cooling step after the ultraviolet irradiation, it is possible to suppress the alignment of the liquid crystal compound from being disturbed by heat generated immediately after the irradiation. As a result, the alignment degree of the liquid crystal compound is increased, and a film having higher rigidity can be obtained. The cooling temperature can be, for example, 20°C or less, and can be 10°C or less. The cooling time can be, for example, 10 seconds or more, and can be 20 seconds or more.
[0051] The thickness of the optically anisotropic layer is preferably 0.5 μm or more. The thickness of the optically anisotropic layer is preferably 10 μm or less, more preferably 5 μm or less. The above upper limit and lower limit can be arbitrarily combined. When the thickness of the optically anisotropic layer is equal to or greater than the lower limit, sufficient durability can be obtained. When the thickness of the optically anisotropic layer is equal to or less than the upper limit, it can contribute to thinning of the circular polarizing plate. The thickness of the optically anisotropic layer can be adjusted so as to obtain the desired in-plane retardation value and thickness direction retardation value of the layer that gives a retardation of λ / 4, the layer that gives a retardation of λ / 2, or the positive C layer.
[0052] When the circularly polarizing plate includes a third optically anisotropic layer, the second optically anisotropic layer and the third optically anisotropic layer can be manufactured by preparing a cured product layer on the alignment film, and laminating the two layers via an adhesive layer. After laminating the two layers, the substrate and the alignment film can be peeled off. The thicknesses of the first optically anisotropic layer 11, the second optically anisotropic layer 12, and the third optically anisotropic layer are each preferably 0.1 μm to 15 μm, more preferably 0.3 μm to 10 μm, and even more preferably 0.5 μm to 8 μm. The thicknesses of the first optically anisotropic layer 11, the second optically anisotropic layer 12, and the third optically anisotropic layer may be the same or different from each other.
[0053] (Polarizer) The polarizer may be an absorption-type polarizer that absorbs linearly polarized light having a vibration plane parallel to its absorption axis and transmits linearly polarized light having a vibration plane perpendicular to the absorption axis (parallel to the transmission axis). As the polarizer, a polarizer in which a dichroic dye is adsorbed and aligned on a uniaxially stretched polyvinyl alcohol-based resin film can be suitably used. The polarizer can be produced by a method including, for example, a step of uniaxially stretching a polyvinyl alcohol-based resin film; a step of dyeing the polyvinyl alcohol-based resin film with the dichroic dye to adsorb the dichroic dye; a step of treating the polyvinyl alcohol-based resin film with the adsorbed dichroic dye with a crosslinking liquid such as an aqueous boric acid solution; and a step of washing with water after the treatment with the crosslinking liquid.
[0054] As the polyvinyl alcohol resin, a saponified polyvinyl acetate resin can be used. As the polyvinyl acetate resin, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate, copolymers of vinyl acetate with other monomers copolymerizable therewith can be mentioned. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group.
[0055] In this specification, "(meth)acrylic" means at least one selected from acrylic and methacrylic. The same applies to "(meth)acryloyl", "(meth)acrylate", etc.
[0056] The saponification degree of the polyvinyl alcohol resin is usually 85 mol% or more and 100 mol% or less, and preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the polyvinyl alcohol resin is usually 1000 or more and 10000 or less, and preferably 1500 or more and 5000 or less. The average polymerization degree of the polyvinyl alcohol resin can be determined in accordance with JIS K 6726.
[0057] Such a polyvinyl alcohol-based resin is used as a raw film for a polarizer. The method for forming the polyvinyl alcohol-based resin is not particularly limited, and a known method is used. The thickness of the polyvinyl alcohol-based raw film is not particularly limited, but in order to make the thickness of the polarizer 15 μm or less, it is preferable to use one having a thickness of 5 μm or more and 35 μm or less. More preferably, it is 20 μm or less.
[0058] The uniaxial stretching of the polyvinyl alcohol-based resin film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during a crosslinking treatment. The uniaxial stretching may also be performed in a plurality of these stages.
[0059] In the uniaxial stretching, the film may be stretched uniaxially between rolls having different peripheral speeds, or may be stretched uniaxially using a heated roll. The uniaxial stretching may be dry stretching in which stretching is performed in the atmosphere, or wet stretching in which stretching is performed in a state where the polyvinyl alcohol-based resin film is swollen using a solvent or water. The stretching ratio is usually 3 times or more and 8 times or less.
[0060] As a method for dyeing a polyvinyl alcohol-based resin film with a dichroic dye, for example, a method of immersing the film in an aqueous solution containing the dichroic dye is adopted. As the dichroic dye, iodine or a dichroic organic dye is used. It is preferable that the polyvinyl alcohol-based resin film is immersed in water before the dyeing process.
[0061] As a crosslinking treatment after dyeing with a dichroic dye, a method of immersing the dyed polyvinyl alcohol resin film in an aqueous solution containing boric acid is usually adopted. When iodine is used as the dichroic dye, the aqueous solution containing boric acid preferably contains potassium iodide.
[0062] The thickness of the polarizer is usually 30 μm or less, preferably 15 μm or less, more preferably 13 μm or less, further preferably 10 μm or less, and particularly preferably 8 μm or less. The thickness of the polarizer is usually 2 μm or more, and preferably 3 μm or more.
[0063] As the polarizer, for example, as described in JP 2016-170368 A, a dichroic dye may be oriented in a cured film in which a liquid crystal compound is polymerized. As the dichroic dye, a dye having absorption in a wavelength range of 380 nm or more and 800 nm or less may be used, and it is preferable to use an organic dye. As the dichroic dye, for example, an azo compound may be used. The liquid crystal compound is a liquid crystal compound that can be polymerized while being oriented, and can have a polymerizable group in the molecule. In addition, as described in WO2011 / 024891, a polarizer may be formed from a dichroic dye having liquid crystal properties.
[0064] (Protective film) The circular polarizing plate may have one or more protective films. The protective film may have a function of protecting the optical anisotropy, the polarizer, etc. The protective film may be disposed, for example, on one or both sides of at least one of the optically anisotropic layer and the polarizer, and is preferably disposed on at least one of the opposite side of the polarizer side of the optically anisotropic layer and the viewing side of the polarizer, and more preferably disposed on at least one of the opposite side of the polarizer side of the first optically anisotropic layer and the viewing side of the polarizer. The optically anisotropic layer or the polarizer and the protective film may be bonded together, for example, via an adhesive layer described later. Hereinafter, a laminate consisting of a polarizer and a protective film is also referred to as a linear polarizing plate.
[0065] When the circular polarizing plate is substantially rectangular and the protective film is a stretched film, it is preferable that the stretching direction of the protective film and the short side direction of the circular polarizing plate are substantially parallel. When the stretching direction and the short side direction are in such a relationship, the hue change of the circular polarizing plate tends to be small in a high temperature environment regardless of the direction of the slow axis of the retardation film. When the stretching direction of the protective film is parallel to the short side, the contraction force in the stretching direction of the protective film due to the stretch relaxation of the polarizer and the protective film in a high temperature environment is smaller than when the stretching direction is parallel to the long side, and it is considered that the hue change is small.
[0066] The stretching direction of the protective film and the short side direction of the circular polarizer being substantially parallel includes not only the case where they are strictly parallel, but also the case where the angle between them is 0±10°. The angle between the stretching direction of the protective film and the short side direction of the circular polarizer is preferably 0±5°.
[0067] The protective film can be a film made of a light-transmitting (preferably optically transparent) thermoplastic resin, for example, a polyolefin resin such as a chain polyolefin resin (such as a polypropylene resin) or a cyclic polyolefin resin (such as a norbornene resin); a cellulose resin such as triacetyl cellulose or diacetyl cellulose; a polyester resin such as polyethylene terephthalate or polybutylene terephthalate; a polycarbonate resin; a (meth)acrylic resin such as a methyl methacrylate resin; a polystyrene resin; a polyvinyl chloride resin; an acrylonitrile-butadiene-styrene resin; an acrylonitrile-styrene resin; a polyvinyl acetate resin; a polyvinylidene chloride resin; a polyamide resin; a polyacetal resin; a modified polyphenylene ether resin; a polysulfone resin; a polyethersulfone resin; a polyarylate resin; a polyamideimide resin; a polyimide resin, or the like.
[0068] Examples of linear polyolefin resins include linear olefin homopolymers such as polyethylene resins (polyethylene resins which are homopolymers of ethylene, and copolymers mainly composed of ethylene) and polypropylene resins (polypropylene resins which are homopolymers of propylene, and copolymers mainly composed of propylene), as well as copolymers composed of two or more types of linear olefins.
[0069] Cyclic polyolefin resin is a general term for resins polymerized with cyclic olefin as a polymerization unit, and examples thereof include resins described in JP-A-1-240517, JP-A-3-14882, JP-A-3-122137, etc. Specific examples of cyclic polyolefin resins include ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers (typically random copolymers) of cyclic olefins and chain olefins such as ethylene and propylene, and graft polymers modified with unsaturated carboxylic acids or derivatives thereof, as well as hydrogenated products thereof. Among these, norbornene resins using norbornene monomers such as norbornene or polycyclic norbornene monomers as cyclic olefins are preferably used.
[0070] The polyester resin is a resin having an ester bond, excluding the cellulose ester resin described below, and is generally made of a polycondensate of a polyvalent carboxylic acid or its derivative and a polyhydric alcohol. As the polyvalent carboxylic acid or its derivative, a divalent dicarboxylic acid or its derivative can be used, for example, terephthalic acid, isophthalic acid, dimethyl terephthalate, and dimethyl naphthalenedicarboxylate. As the polyhydric alcohol, a divalent diol can be used, for example, ethylene glycol, propanediol, butanediol, neopentyl glycol, and cyclohexanedimethanol. A representative example of the polyester resin is polyethylene terephthalate, which is a polycondensate of terephthalic acid and ethylene glycol.
[0071] The (meth)acrylic resin is a resin whose main constituent monomer is a compound having a (meth)acryloyl group. Specific examples of the (meth)acrylic resin include poly(meth)acrylic acid ester such as polymethyl methacrylate; methyl methacrylate-(meth)acrylic acid copolymer; methyl methacrylate-(meth)acrylic acid ester copolymer; methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymer; methyl (meth)acrylate-styrene copolymer (MS resin, etc.); copolymers of methyl methacrylate and a compound having an alicyclic hydrocarbon group (e.g., methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylate copolymer, etc.). Preferably, poly(meth)acrylic acid C such as polymethyl (meth)acrylate is used. 1-6 A polymer containing an alkyl ester as a main component is used, and more preferably a methyl methacrylate-based resin containing methyl methacrylate as a main component (50% by mass or more and 100% by mass or less, preferably 70% by mass or more and 100% by mass or less).
[0072] The cellulose ester resin is an ester of cellulose and a fatty acid. Specific examples of the cellulose ester resin include cellulose triacetate, cellulose diacetate, cellulose tripropionate, and cellulose dipropionate. In addition, copolymers thereof and those in which a part of the hydroxyl group is modified with another substituent are also included. Among these, cellulose triacetate (triacetyl cellulose) is particularly preferred.
[0073] Polycarbonate resins are engineering plastics made of polymers in which monomer units are bonded via carbonate groups.
[0074] The thickness of the protective film is usually 1 μm or more and 100 μm or less, but from the viewpoints of strength, handleability, etc., it is preferably 5 μm or more and 60 μm or less, more preferably 10 μm or more and 55 μm or less, and even more preferably 15 μm or more and 40 μm or less.
[0075] When the circularly polarizing plate has two or more protective films, the protective films may be made of the same type of thermoplastic resin or different types of thermoplastic resin. The thicknesses may be the same or different. Furthermore, the retardation properties may be the same or different.
[0076] As described above, at least one of the protective films may have a surface treatment layer (coating layer) such as a hard coat layer, an antiglare layer, a light diffusion layer, an antireflection layer, a low refractive index layer, an antistatic layer, or an antifouling layer on its outer surface (the surface opposite to the polarizer). The thickness of the protective film includes the thickness of the surface treatment layer.
[0077] The protective film can be attached to other layers such as an optically anisotropic layer and a polarizer via an adhesive layer described below.
[0078] (Adhesive layer) The adhesive layer is disposed between the first optically anisotropic layer 11 and the polarizer 10, and between the polarizer 10 and the second optically anisotropic layer 12 or the third optically anisotropic layer. The adhesive layer can be an adhesive layer or a pressure-sensitive adhesive layer. The adhesive layer can be a single layer or multiple layers.
[0079] The adhesive layer may be formed of a water-based adhesive, an active energy ray-curable adhesive, or a heat-curable adhesive, preferably a water-based adhesive or an active energy ray-curable adhesive. The pressure-sensitive adhesive layer may be formed of any of the adhesives described below.
[0080] Examples of the aqueous adhesive include an adhesive made of an aqueous polyvinyl alcohol resin solution, an aqueous two-liquid urethane emulsion adhesive, and the like. Among them, an aqueous adhesive made of an aqueous polyvinyl alcohol resin solution is preferably used. Examples of the polyvinyl alcohol resin include a vinyl alcohol homopolymer obtained by saponifying polyvinyl acetate, which is a homopolymer of vinyl acetate, a polyvinyl alcohol copolymer obtained by saponifying a copolymer of vinyl acetate and another monomer copolymerizable therewith, and a modified polyvinyl alcohol polymer in which the hydroxyl groups of these are partially modified. The aqueous adhesive may contain a crosslinking agent such as an aldehyde compound (such as glyoxal), an epoxy compound, a melamine compound, a methylol compound, an isocyanate compound, an amine compound, or a polyvalent metal salt.
[0081] When a water-based adhesive is used, it is preferable to carry out a drying step to remove water contained in the water-based adhesive after laminating the layers together. After the drying step, a curing step may be carried out, for example, at a temperature of 20° C. or higher and 45° C. or lower.
[0082] The active energy ray-curable adhesive is an adhesive containing a curable compound that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, and is preferably an ultraviolet ray-curable adhesive.
[0083] The curable compound may be a cationic polymerizable curable compound or a radical polymerizable curable compound. Examples of the cationic polymerizable curable compound include an epoxy compound (a compound having one or more epoxy groups in the molecule), an oxetane compound (a compound having one or more oxetane rings in the molecule), or a combination thereof. Examples of the radical polymerizable curable compound include a (meth)acrylic compound (a compound having one or more (meth)acryloyloxy groups in the molecule), other vinyl compounds having a radical polymerizable double bond, or a combination thereof. A cationic polymerizable curable compound and a radical polymerizable curable compound may be used in combination. An active energy ray curable adhesive usually further includes at least one of a cationic polymerization initiator and a radical polymerization initiator for initiating the curing reaction of the curable compound.
[0084] The adhesive layer can be composed of an adhesive composition mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin. Among them, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is preferable. The adhesive composition may be an active energy ray curable type or a heat curable type. The thickness of the adhesive layer is usually 3 μm or more and 30 μm or less, and preferably 3 μm or more and 25 μm or less.
[0085] As the (meth)acrylic resin (base polymer) used in the pressure-sensitive adhesive composition, for example, a polymer or copolymer containing one or more (meth)acrylic acid esters as monomers, such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, is preferably used. It is preferable to copolymerize a polar monomer into the base polymer. Examples of the polar monomer include monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like, such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.
[0086] The adhesive composition may contain only the base polymer, but usually further contains a crosslinking agent. Examples of the crosslinking agent include divalent or higher metal ions that form a carboxylate metal salt with a carboxyl group; polyamine compounds that form an amide bond with a carboxyl group; polyepoxy compounds or polyols that form an ester bond with a carboxyl group; and polyisocyanate compounds that form an amide bond with a carboxyl group. Among them, polyisocyanate compounds are preferred.
[0087] In order to enhance adhesion, a surface activation treatment may be performed on at least one of the bonding surfaces of the adhesive layer and the layer to be bonded to the adhesive layer. Examples of the surface activation treatment include dry treatments such as corona treatment, plasma treatment, discharge treatment (glow discharge treatment, etc.), flame treatment, ozone treatment, UV ozone treatment, and ionizing active ray treatment (ultraviolet ray treatment, electron beam treatment, etc.); and wet treatments such as ultrasonic treatment using a solvent such as water or acetone, saponification treatment, and anchor coat treatment. These surface activation treatments may be performed alone or in combination of two or more.
[0088] When two or more adhesive layers are provided, the adhesives used in the adhesive layers may be the same or different. When two or more pressure-sensitive adhesive layers are provided, the pressure-sensitive adhesives used in the pressure-sensitive adhesive layers may be the same or different.
[0089] (Front plate) The front plate is disposed so as to be the viewing side when the circular polarizer 100 is attached to an image display element. The front plate is preferably disposed so as to be the outermost surface of the viewing side of the circular polarizer 100. When a circular polarizer having a front plate on the outermost surface of the viewing side is used in an image display device, the circular polarizer is disposed so that the front plate is the outermost surface of the viewing side of the image display device. The front plate is attached via an adhesive layer.
[0090] Examples of the front plate include glass and resin film having a hard coat layer on at least one side. Examples of the glass that can be used include highly transparent glass and reinforced glass. In particular, when using a thin transparent surface material, chemically reinforced glass is preferred. The thickness of the glass can be, for example, 20 μm or more and 5 mm or less.
[0091] A front panel including a hard coat layer on at least one side of a resin film can have flexible properties, unlike conventional glass, and the thickness of the hard coat layer is not particularly limited, and may be, for example, 5 μm or more and 20 μm or less.
[0092] The resin film may be a film formed of a polymer such as a cycloolefin derivative having a unit of a monomer containing a cycloolefin such as norbornene or a polycyclic norbornene monomer, cellulose (diacetyl cellulose, triacetyl cellulose, acetyl cellulose butyrate, isobutyl ester cellulose, propionyl cellulose, butyryl cellulose, acetyl propionyl cellulose), ethylene-vinyl acetate copolymer, polycycloolefin, polyester, polystyrene, polyamide, polyetherimide, polyacrylic, polyimide, polyamideimide, polyethersulfone, polysulfone, polyethylene, polypropylene, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl acetal, polyether ketone, polyether ether ketone, polyethersulfone, polymethyl methacrylate, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyurethane, or epoxy. The resin film may be an unstretched, uniaxially or biaxially stretched film. Each of these polymers may be used alone or in a mixture of two or more. As the resin film, polyamideimide film or polyimide film excellent in transparency and heat resistance, uniaxially or biaxially stretched polyester film, cycloolefin derivative film excellent in transparency and heat resistance and capable of handling large-sized films, polymethyl methacrylate film, and triacetyl cellulose and isobutyl ester cellulose films with no transparency and optical anisotropy are preferred. The thickness of the resin film may be 5 μm or more and 200 μm or less, preferably 20 μm or more and 100 μm or less.
[0093] The hard coat layer can be formed by curing a hard coat composition containing a reactive material that forms a crosslinked structure by irradiation with light or heat energy. The hard coat composition can simultaneously contain a photocurable (meth)acrylate monomer or oligomer and a photocurable epoxy monomer or oligomer. The photocurable (meth)acrylate monomer can include one or more selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, and polyester (meth)acrylate. The epoxy (meth)acrylate can be obtained by reacting an epoxy compound with a carboxylic acid having a (meth)acryloyl group.
[0094] The hard coat composition may further include at least one selected from the group consisting of a solvent, a photoinitiator, and an additive. The additive may include at least one selected from the group consisting of inorganic nanoparticles, a leveling agent, and a stabilizer, and may further include components commonly used in the art, such as an antioxidant, a UV absorber, a surfactant, a lubricant, and an antifouling agent.
[0095] (Light blocking pattern) The light-shielding pattern may be formed on the polarizer side of the front plate. The light-shielding pattern may be formed on the frame (non-display area) of the image display device to prevent the wiring of the image display device from being visually recognized by the user. The light-shielding pattern may be provided as at least a part of the front plate or the bezel or housing of the display device to which the front plate is applied. The color and material of the light-shielding pattern are not particularly limited, and the light-shielding pattern may be formed of a resin material having various colors such as black, white, and gold. In one embodiment, the thickness of the light-shielding pattern may be in the range of 2 μm to 50 μm, preferably 4 μm to 30 μm, and more preferably 6 μm to 15 μm. In addition, a shape may be imparted to the light-shielding pattern in order to suppress the inclusion of air bubbles and the visibility of the boundary due to the step between the light-shielding pattern and the display area.
[0096] The circularly polarizing plate 200 shown in FIG. 2 has a protective film 14, an adhesive layer 13, a first optically anisotropic layer 11, an adhesive layer 15, a polarizer 10, an adhesive layer 18, and a second optically anisotropic layer 12 in this order.
[0097] 3 includes, in this order, a first optically anisotropic layer 11, an adhesive layer 13, a linear polarizing plate 16 in which a protective film 14 and a polarizer 10 are laminated, an adhesive layer 15, and a second optically anisotropic layer 12. The adhesive layer that bonds the protective film 14 and the polarizer 10 is not shown.
[0098] 4 has, in this order, a protective film 14, an adhesive layer 13, a first optically anisotropic layer 11, an adhesive layer 15, a polarizer 10, an adhesive layer 18, a third optically anisotropic layer 17, and a second optically anisotropic layer 12. The adhesive layer that bonds the third optically anisotropic layer 17 and the second optically anisotropic layer 12 is not shown.
[0099] 5 includes, in this order, a first optically anisotropic layer 11, an adhesive layer 13, a linear polarizing plate 16 in which a protective film 14 and a polarizer 10 are laminated, an adhesive layer 15, a third optically anisotropic layer 17, and a second optically anisotropic layer 12. The adhesive layer that bonds the protective film 14 and the polarizer 10, and the adhesive layer that bonds the third optically anisotropic layer 17 and the second optically anisotropic layer 12 are not shown.
[0100] (Manufacturing method of circularly polarizing plate) An example of a manufacturing method of a circular polarizing plate 300 will be described with reference to Fig. 6. First, a second optically anisotropic layer 12 is laminated on the polarizer 10 side of a linear polarizing plate 16 via an adhesive layer 15 (Fig. 6(a)). Next, a first optically anisotropic layer 11 is laminated on the protective film 14 side of the linear polarizing plate 16 via an adhesive layer 13, thereby obtaining a circular polarizing plate 300 (Fig. 6(b)). When the second optically anisotropic layer 12 includes an optically anisotropic layer having the optical properties represented by formula (III), it is preferable to laminate the layers so that the angle between the absorption axis of the polarizer 10 and the slow axis of the second optically anisotropic layer 12 is 45°, and the angle between the slow axis of the first optically anisotropic layer 11 and the slow axis of the second optically anisotropic layer 12 is 90°.
[0101] The linear polarizing plate 16 can be produced by laminating the polarizer 10 and the protective film 14 via an adhesive layer. The linear polarizing plate 16 may be produced by preparing a long member, laminating the respective members by roll-to-roll and then cutting them into a predetermined shape, or by cutting the respective members into a predetermined shape and then laminating them together. After laminating the protective film to the polarizer, a heating step or a humidity adjustment step may be carried out.
[0102] The first optically anisotropic layer 11 and the second optically anisotropic layer 12 can be produced, for example, as follows. An alignment film is formed on a substrate, and a coating liquid containing a polymerizable liquid crystal compound is applied onto the alignment film. In a state in which the polymerizable liquid crystal compound is aligned, the polymerizable liquid crystal compound is cured by irradiating with active energy rays. A pressure-sensitive adhesive layer 15 formed on a release film is laminated on the layer of the cured polymerizable liquid crystal compound, and the substrate and / or the alignment film are peeled off. The optically anisotropic layer may be produced by preparing long members, laminating the respective members together by roll-to-roll and then cutting them into a predetermined shape, or by cutting the respective members into a predetermined shape and then laminating them together. The release film is peeled off when the optically anisotropic layer is attached to a polarizer or a linear polarizing plate, to expose the pressure-sensitive adhesive layer.
[0103] <Application> Circularly polarizing plates can be used in various display devices. A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal display devices, organic EL display devices, inorganic electroluminescence (hereinafter also referred to as inorganic EL) display devices, electron emission display devices (e.g., field emission display devices (FEDs) and surface field emission display devices (SEDs)), electronic paper (display devices using electronic ink or electrophoretic elements, plasma display devices, projection display devices (e.g., grating light valve (GLV) display devices, display devices having digital micromirror devices (DMDs)), and piezoelectric ceramic displays. Liquid crystal display devices include both transmissive liquid crystal display devices and semi-transmissive liquid crystal display devices. These display devices may be display devices that display two-dimensional images, or stereoscopic display devices that display three-dimensional images. Circularly polarizing plates can be used particularly effectively in organic EL display devices or inorganic EL display devices. The circularly polarizing plate can be attached to a display element using a pressure-sensitive adhesive layer so that the first optically anisotropic layer is on the viewing side of the display device. The circularly polarizing plate of the present invention can reduce the reflected light when the in-vehicle display light is reflected by the windshield, and can also reduce the color change of the reflected light. In addition, the circularly polarizing plate has excellent light resistance, making it suitable for in-vehicle image display devices.
[0104] 7, an organic EL display device 600 has a layered structure in which a circular polarizer 101 is laminated on an organic EL display element 20 via an adhesive layer 19 laminated on the second optically anisotropic layer 12 side of the circular polarizer 101. A front plate 22 is attached to the circular polarizer 101 via an adhesive layer 21 laminated on the first optically anisotropic layer 11. EXAMPLES
[0105] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.
[0106] [Evaluation of reflected light from display] As shown in Fig. 8, a display 23, a black acrylic plate 25, etc. were arranged. The obtained circular polarizing plate 24 was attached to the viewing side (black acrylic plate 25 side) of the white displaying display 23. Light emitted from the white display 23 was reflected by the black acrylic plate 25, which was placed at an angle of 45° to the display 23. The display 23 was rotated horizontally around an axis 26 perpendicular to the display surface of the display 23 as the axis of rotation, and the black acrylic plate 25 was visually observed from an observation direction 27. A small change in the color of the reflected light was evaluated as A, and a large change in the color of the reflected light was evaluated as B.
[0107] [Evaluation of curl of circular polarizing plate] An acrylic adhesive layer B and a separate film were attached to the second optically anisotropic layer of the circular polarizer obtained in the example. The obtained circular polarizer with adhesive was cut into a size of 200 mm x 100 mm. The cut circular polarizer with adhesive was evaluated for curling. Those that curled were rated B, and those that did not curl were rated A.
[0108] [Light resistance evaluation of circular polarizing plates] An acrylic adhesive layer B and a separate film were attached to the second optically anisotropic layer of the circular polarizer obtained in the example. The obtained circular polarizer with adhesive was cut into a size of 40 mm x 40 mm. The separate film was peeled off and the exposed adhesive was attached to non-alkali glass to obtain glass with a circular polarizer. The obtained sample was subjected to UV exposure of 95,400 kJ / m using a tabletop xenon arc lamp accelerated light resistance tester (ATLAS, SUNTEST XLS+). 2 The circular polarizer was irradiated with light at a wavelength of 450 nm, 550 nm, and 650 nm. The in-plane retardation values of the circular polarizer after irradiation with light at wavelengths of 450 nm, 550 nm, and 650 nm were measured using KOBRA-WR manufactured by Oji Scientific Instruments Co., Ltd. The ΔRe(550) of the second optically anisotropic layer was calculated from the obtained data. ΔRe(550) = Re(550) after test - initial Re(550) Evaluation criteria: A: Those having ΔRe(550) smaller than that of Comparative Example 1 were judged to have good light resistance. B: When ΔRe(550) was equal to or greater than that of Comparative Example 1, the light resistance was determined to be low.
[0109] [Optical anisotropic layer A] Five parts of a photoalignment material (weight average molecular weight: 30,000) having the following structure was mixed with 95 parts of cyclopentanone (solvent), and the resulting mixture was stirred at 80° C. for 1 hour to obtain a composition for forming an alignment film.
[0110] To 100 parts of a mixture of polymerizable liquid crystal compound a and polymerizable liquid crystal compound b shown below in a mass ratio of 90:10, 1.0 part of a leveling agent (F-556; manufactured by DIC Corporation) and 6 parts of a polymerization initiator, 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one ("Irgacure 369 (Irg369)", manufactured by BASF Japan Ltd.) were added.
[0111] Furthermore, N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration became 13%, and the mixture was stirred at 80° C. for 1 hour to obtain a liquid crystal cured film-forming composition.
[0112] Polymerizable liquid crystal compound a was produced by the method described in JP-A-2010-31223. Polymerizable liquid crystal compound b was produced according to the method described in JP-A-2009-173893. The molecular structures of each compound are shown below.
[0113] (Polymerizable liquid crystal compound a) [ka]
[0114] (Polymerizable liquid crystal compound b) [ka]
[0115] (Production of a laminate consisting of a substrate, an alignment film, and a layer of a cured polymerizable liquid crystal compound) A 50 μm thick cycloolefin film (trade name "ZF-14-50" manufactured by Zeon Corporation) was subjected to corona treatment as a substrate. The composition for forming an alignment film was applied to the corona-treated surface using a bar coater. The coating film was dried at 80°C for 1 minute. The dried coating film was irradiated with polarized UV at an axial angle of 45° using a polarized UV irradiation device (trade name "SPOT CURE SP-9" manufactured by Ushio Inc.) to obtain an alignment film. The polarized UV irradiation was performed with an integrated light amount of 100 mJ / cm at a wavelength of 313 nm. 2 It was carried out so that it became.
[0116] Next, a liquid crystal cured film-forming composition was applied onto the alignment film using a bar coater. The applied film was dried at 120°C for 1 minute. The dried applied film was irradiated with ultraviolet light using a high-pressure mercury lamp (trade name: "Uniquer VB-15201BY-A" by Ushio Inc.). The ultraviolet light irradiation process was carried out with an integrated light amount of 250 mJ / cm at a wavelength of 365 nm. 2 Immediately after irradiation, the cured film was placed in an oven set at 5° C. for 20 seconds as a cooling step. Immediately after removing from the oven, the ultraviolet irradiation step and cooling step were carried out again to obtain a laminate consisting of the substrate, the alignment film, and a layer of cured polymerizable liquid crystal compound.
[0117] (Measurement of phase difference value) An adhesive layer was laminated on the layer of the laminate where the polymerizable liquid crystal compound was cured. The laminate was attached to glass via the adhesive layer. Thereafter, the substrate of the laminate was peeled off to obtain a sample for evaluating the retardation value. As a result, the layer where the polymerizable liquid crystal compound was cured had retardation values Re(λ) at each wavelength of Re(450)=121 nm, Re(550)=142 nm, and Re(650)=146 nm. As a result, Re(450) / Re(550)=0.85 and Re(650) / Re(550)=1.03 were calculated. The layer where the polymerizable liquid crystal compound was cured was a layer that gave a retardation of λ / 4.
[0118] [Optical anisotropic layer B] A first optically anisotropic layer (H) [Re(550)=250 nm] was prepared as described in paragraphs 0026 to 0051 of JP2015-187717A.
[0119] [Optical anisotropic layer C] A second optically anisotropic layer (Q) [Re(550)=120 nm] was prepared as described in paragraphs 0053 to 0062 of JP2015-187717A.
[0120] [Optical anisotropic layer D] A stretched film made of a norbornene resin with a thickness of 25 μm was prepared. The retardation values were measured to find that Re(450) = 99.0 nm, Re(550) = 98.6 nm, and Re(650) = 98.5 nm, and the calculated values were Re(450) / Re(550) = 1.004 and Re(650) / Re(550) = 0.999.
[0121] [Optical anisotropic layer E] A polyvinyl alcohol film (thickness 0.1 μm) was formed on the surface of a substrate (TAC film, thickness 40 μm). The surface of the polyvinyl alcohol film was rubbed with a rubbing cloth in a direction at an angle of 45° to the longitudinal direction of the substrate to prepare an alignment substrate.
[0122] A coating liquid was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF, product name Paliocolor LC242) and 0.5 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by Ciba Specialty Chemicals, product name Irgacure 907, containing 1% benzotriazole-based UV absorber) in 40 g of toluene.
[0123] The coating liquid was applied to the surface of the alignment substrate obtained above using a bar coater, and then dried at 100° C. for 1 minute. The coating film was irradiated with ultraviolet light using a high-pressure mercury lamp to obtain an optically anisotropic layer E. The ultraviolet light was irradiated in a nitrogen atmosphere, and the integrated light amount at a wavelength of 365 nm was 1200 mJ / cm 2 . 2The thickness of the obtained optically anisotropic layer E was measured by a laser microscope and found to be 973 nm. The orientation angle was 45° with respect to the longitudinal direction of the substrate. The retardation values of the optically anisotropic layer E were measured and found to be Re(450)=145 nm, Re(550)=135 nm, and Re(650)=132 nm. The relationship between the in-plane retardation values at each wavelength was as follows: Re(450) / Re(550)=1.07 Re(650) / Re(550)=0.98
[0124] [Linear polarizer A] A polarizer was prepared in which iodine was adsorbed and aligned in a PVA-based resin. The thickness of this polarizer was 7 μm. A cycloolefin polymer (COP) film (ZF-14, manufactured by Zeon Corporation) was attached to one surface of the polarizer. The thickness of the COP film was 13 μm. In this manner, a linear polarizing plate A having a protective film on one surface of the polarizer was produced.
[0125] [Linear polarizer B] A composition for forming a polarizer was prepared, which contains a polymerizable liquid crystal compound represented by the following formula (1-6), a polymerizable liquid crystal compound represented by the following formula (1-7), and azo dyes described in Examples of JP2013-101328A and represented by the following formulas (2-1a), (2-1b), and (2-3a). [ka] [ka] [ka] [ka] [ka]
[0126] An alignment film was formed on the substrate. A composition for forming a polarizing layer was applied onto the alignment film by a bar coating method. The coating film was irradiated with ultraviolet light to harden the polymerizable liquid crystal compound. In this manner, a linear polarizing plate B was produced.
[0127] [Acrylic adhesive layer A] A 5 μm thick sheet-shaped adhesive (manufactured by Lintec Corporation) was prepared.
[0128] [Acrylic adhesive layer B] A sheet-shaped adhesive (manufactured by Lintec Corporation) having a thickness of 25 μm was prepared.
[0129] <Example 1> An acrylic pressure-sensitive adhesive layer A was attached to the polarizer side surface of the linear polarizing plate A. The surface of the optically anisotropic layer A on the side of the layer containing the cured polymerizable liquid crystal compound was attached via this pressure-sensitive adhesive layer so that the angle between the absorption axis of the polarizer and the slow axis of the optically anisotropic layer A (second optically anisotropic layer) was 45°. An acrylic pressure-sensitive adhesive layer A was attached to the COP side surface of the linear polarizing plate A. The surface of the optically anisotropic layer A on the side of the layer containing the cured polymerizable liquid crystal compound was attached via this pressure-sensitive adhesive layer so that the angle between the slow axis of the second optically anisotropic layer and the slow axis of the optically anisotropic layer A (first optically anisotropic layer) was 90°. In this manner, a circular polarizing plate comprising, in this order, an optically anisotropic layer A (first optically anisotropic layer), a polarizing plate A, and an optically anisotropic layer A (second optically anisotropic layer) was prepared.
[0130] <Example 2> The optically anisotropic layer B (third optically anisotropic layer) and the optically anisotropic layer C (second optically anisotropic layer) were bonded to each other with the acrylic pressure-sensitive adhesive layer A to prepare an optically anisotropic layer laminate. A circular polarizing plate was prepared in the same manner as in Example 1, except that, instead of bonding optically anisotropic layer A (second optically anisotropic layer) so that the angle between the absorption axis of the polarizer and the slow axis of optically anisotropic layer A was 45°, the surface of the optically anisotropic layer B (third optically anisotropic layer) side of the optically anisotropic layer laminate and the surface of the linear polarizing plate A on the polarizer side were bonded via an acrylic adhesive layer A so that the angle between the absorption axis of the polarizer and the slow axis of optically anisotropic layer C (second optically anisotropic layer) of the optically anisotropic layer laminate was 45°.
[0131] <Example 3> A circular polarizing plate was produced in the same manner as in Example 1, except that polarizing plate B was used instead of linear polarizing plate A.
[0132] <Example 4> A circular polarizing plate was prepared in the same manner as in Example 1, except that the optically anisotropic layer A (first optically anisotropic layer) was bonded so that the angle between the slow axis of the optically anisotropic layer A (second optically anisotropic layer) and the slow axis of the optically anisotropic layer A (first optically anisotropic layer) was 0°.
[0133] <Comparative Example 1> A circularly polarizing plate was produced in the same manner as in Example 1, except that the optically anisotropic layer D was used instead of the optically anisotropic layer A (first optically anisotropic layer).
[0134] <Comparative Example 2> A circularly polarizing plate was produced in the same manner as in Example 1, except that the optically anisotropic layer E was used instead of the optically anisotropic layer A (first optically anisotropic layer).
[0135] [Table 1] [Explanation of symbols]
[0136] 10 polarizer, 11 first optically anisotropic layer, 12 second optically anisotropic layer, 13, 15, 18, 21 adhesive layer, 19 pressure-sensitive adhesive layer, 14 protective film, 16 linear polarizing plate, 17 third optically anisotropic layer, 20 organic EL display element, 22 front plate, 23 display, 24 circular polarizing plate, 25 black acrylic plate, 26 axis, 27 observation direction, 100, 101, 200, 300, 400, 500 circular polarizing plate, 600 organic EL display device.
Claims
1. A circularly polarizing plate having, from a viewing side, a first optically anisotropic layer, a polarizer, and a second optically anisotropic layer in this order, The first optically anisotropic layer is represented by the following formulas (I), (II) and (III): Re(450) / Re(550)≦1.00 (I) 1.00≦Re(650) / Re(550) (II) 90nm≦Re(550)≦180nm (III) [wherein Re(450) represents an in-plane retardation value of the optically anisotropic layer at a wavelength of 450 nm, Re(550) represents the in-plane retardation value of the optically anisotropic layer at a wavelength of 550 nm; Re(650) represents the in-plane retardation value of the optically anisotropic layer at a wavelength of 650 nm. The optical property is represented by Further comprising a third optically anisotropic layer, the third optically anisotropic layer is disposed between the polarizer and the second optically anisotropic layer or on the opposite side of the second optically anisotropic layer to the polarizer side, the first optically anisotropic layer, the second optically anisotropic layer and the third optically anisotropic layer are layers containing a polymer obtained by polymerizing a polymerizable liquid crystal compound in an aligned state, A circularly polarizing plate having a front plate disposed on the outermost surface on the side of the first optically anisotropic layer with respect to the polarizer (excluding the case where two or more optically anisotropic layers are included on the viewing side of the polarizer).
2. The circularly polarizing plate according to claim 1 , wherein the second optically anisotropic layer has the optical property represented by formula (III).
3. The circularly polarizing plate according to claim 1 or 2, wherein the second optically anisotropic layer further has the formula (I) and the formula (II).
4. The third optically anisotropic layer is represented by the following formula (IV): 200nm≦Re(550)≦320nm (IV) 4. The circularly polarizing plate according to claim 1, having optical properties represented by the formula: wherein Re(550) represents an in-plane retardation value of the optically anisotropic layer at a wavelength of 550 nm.
5. 5. The circular polarizing plate according to claim 1, wherein the angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer is 90°±10°.
6. 6. The circularly polarizing plate according to claim 1, wherein the polarizer is a uniaxially stretched polyvinyl alcohol-based resin film having a dichroic dye adsorbed and aligned thereon.
7. 6. The circularly polarizing plate according to claim 1, wherein the polarizer is a polarizer in which a dichroic dye is oriented in a cured film formed by polymerizing a polymerizable liquid crystal compound.
8. 8. An organic electroluminescence display device comprising the circular polarizing plate according to claim 1, and an organic EL display element disposed on the second optically anisotropic layer side with respect to the polarizer of the circular polarizing plate.
9. An in-vehicle display comprising the organic electroluminescence display device according to claim 8 .
Citation Information
Patent Citations
Polarizing film, optical film laminate including the same, extended laminate to be used for manufacturing optical film laminate including polarizing film, method for manufacturing the same, and organic el display device having polarizing film
JP2012133312A
Method for manufacturing circularly polarizing plate
JP2015187717A
Polarizing plate and display device
JP2019185007A
Drying device and drying method
WO2016084247A1
Optically anisotropic laminate, circularly polarizing plate, and image display device
WO2017170360A1